Sex Differences in Sex Hormone Profiles and Prediction of Consciousness Recovery After Severe Traumatic Brain Injury - Zhong, Yu H.; Wu, Hong Y.; He, Ren H.; Zheng, Bi E.; Fan, Jian Z. (Frontiers in Endocrinology, 2019)
Objective: The clinical course of unconsciousness after traumatic brain injury (TBI) is commonly unpredictable and it remains a challenge with limited therapeutic options. The aim of this study was to evaluate the early changes in serum sex hormone levels after severe TBI (sTBI) and the use of these hormones to predict recovery from unconsciousness with regard to sex. Methods: We performed a retrospective study including patients with sTBI. A statistical of analysis of serum sex hormone levels and recovery of consciousness at six months was made to identify the effective prognostic indicators. Results: Fifty-five male patients gained recovery of consciousness, and 37 did not. Of the female patients, 22 out of 32 patients regained consciousness. Male patients (n = 92) with sTBI, compared with healthy subjects (n = 60), had significantly lower levels of FSH, testosterone and progesterone and higher levels of prolactin. Female patients (n = 32) with sTBI, compared with controls (n = 60), had significantly lower levels of estradiol, progesterone and testosterone and significantly higher levels of FSH and prolactin. Testosterone significantly predicted consciousness recovery in male patients. Normal or elevated testosterone levels in the serum were associated with a reduced risk of the unconscious state in male patients with sTBI. For women patients with sTBI, sex hormone levels did not contribute to the prediction of consciousness recovery. Conclusion: These findings indicate that TBI differentially affects the levels of sex-steroid hormones in men and women patients. Plasma levels of testosterone could be a good candidate blood marker to predict recovery from unconsciousness after sTBI for male patients.